2020
DOI: 10.1158/1078-0432.ccr-19-3874
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Age Increases Immunosuppression in the Brain and Decreases Immunotherapeutic Efficacy in Subjects with Glioblastoma

Abstract: ◥Purpose: Wild-type isocitrate dehydrogenase-expressing glioblastoma (GBM) is the most common and aggressive primary brain tumor with a median age at diagnosis of ≥65 years. It accounts for approximately 90% of all GBMs and has a median overall survival (OS) of <15 months. Although immune checkpoint blockade (ICB) therapy has achieved remarkable survival benefits in a variety of aggressive malignancies, similar success has yet to be achieved for GBM among phase III clinical trials to date. Our study aimed to u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 67 publications
2
53
0
Order By: Relevance
“…They observed that the activation of MDSCs was dependent on the presence of FoxP3 + -positive Tregs. Recently, Ladomersky et al [187] reported that the age-related decrease in the efficacy of immunotherapy against mouse glioblastoma was associated with an increase in the expression of IDO protein with aging in mouse brain. However, the age-related immunosuppression was not reversed by the treatment with the pharmacological inhibitor of IDO enzyme.…”
Section: Ido and Kynurenine Signalingmentioning
confidence: 99%
“…They observed that the activation of MDSCs was dependent on the presence of FoxP3 + -positive Tregs. Recently, Ladomersky et al [187] reported that the age-related decrease in the efficacy of immunotherapy against mouse glioblastoma was associated with an increase in the expression of IDO protein with aging in mouse brain. However, the age-related immunosuppression was not reversed by the treatment with the pharmacological inhibitor of IDO enzyme.…”
Section: Ido and Kynurenine Signalingmentioning
confidence: 99%
“…Several studies demonstrate that immune senescence, which is distinct from exhaustion, is more exaggerated in cancer patients compared with age-matched adults and is linked to worse prognosis in several solid cancers (25)(26)(27). Although studies have shown that immunosuppression increases in the brain with advanced age and inhibits antiglioma immunity in older adults (28,29) there are no studies formally studying/characterizing CD8 1 CD28 -T cell dysfunction in GBM patients.…”
Section: Introductionmentioning
confidence: 99%
“…T cell anti-tumour activity can also be inhibited by indoleamine 2,3-dioxygenase (IDO), an enzyme present in the TME responsible for catalysing the oxidation of tryptophan to downstream metabolites belonging to the kynurenine pathway. This can, through a variety of mechanisms, lead to T cell dysfunction, an effect that is particularly pronounced in the setting of advanced age [ 35 , 36 ]. Furthermore, Tregs are enriched in glioblastoma lesions compared to peripheral blood, and are expected to further inhibit the function of effector T cells, as well as NK cells [ 19 , 37 ].…”
Section: The Glioblastoma Tmementioning
confidence: 99%